2007
DOI: 10.1016/j.nimb.2007.01.148
|View full text |Cite
|
Sign up to set email alerts
|

Ion-optics calculations and preliminary precision estimates of the gas-capable ion source for the 1-MV LLNL BioAMS spectrometer

Abstract: Ion-optics calculations were performed for a new ion source and injection beam line. This source, which can accept both solid and gaseous targets, will be installed onto the 1-MV BioAMS spectrometer at the Center for Accelerator Mass Spectrometry, located at Lawrence Livermore National Laboratory and will augment the current LLNL cesium-sputter solid sample ion source. The ion source and its associated injection beam line were designed to allow direct quantification of 14 C/ 12 C and 3 H/ 1 H isotope ratios fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…An efficient ion source that accepts gaseous samples will provide a spectrometer capable of zeptomole quantitation [44]. Our demonstration of LC separation from a few cells shows that AMS has the sensitivity to quantify metabolites from individual cells, providing one of the critical data sets required for the advancement of quantitative biology.…”
Section: Cellular Metabolismmentioning
confidence: 99%
“…An efficient ion source that accepts gaseous samples will provide a spectrometer capable of zeptomole quantitation [44]. Our demonstration of LC separation from a few cells shows that AMS has the sensitivity to quantify metabolites from individual cells, providing one of the critical data sets required for the advancement of quantitative biology.…”
Section: Cellular Metabolismmentioning
confidence: 99%
“…The new ion source and its associated injection beam line is attached through an existing port of a 45° electrostatic analyzer which can rotate to enable the operation of either ion source. The new injection beam line has been designed to allow for the direct quantification of either 14 C/ 12 C or 3 H/ 1 H isotopic ratios [7; 8; 9; 10]. This configuration increases our 3 H-AMS measurement throughput as it eliminates slow magnetic field switching of the injector magnet that is required when using our other source.…”
Section: Descriptionmentioning
confidence: 99%
“…It was also not considered realistic to switch the energy of the ions entering the magnet in order to use the existing Faraday cups. The approach that was adopted is not unlike that taken at LLNL for their BioAMS spectrometer [5], which has a magnetic sector ahead of the injection magnet that apparently can cleanly resolve hydrogen and tritium ions without changing settings. In our instrument, the corresponding magnetic sector is present in a Wien filter.…”
Section: Modification Of the Instrument For Simultaneous Detection Ofmentioning
confidence: 99%
“…Detailed analysis indicated that with selection of an appropriate pair of permanent magnets for the Wien filter, space available in the vacuum system would permit installation of a Faraday cup to collect 1 H ion current ahead of the injection magnet. It is recognized that this configuration, in which the hydrogen ion current is measured before the accelerator will exhibit less precision than one in which both isotopes are accelerated, but such a system is expected to have more than adequate precision for bio-AMS, as suggested in [5]…”
Section: Modification Of the Instrument For Simultaneous Detection Ofmentioning
confidence: 99%